Mechanical Control of Heliothis virescens and Pseudomonas syringae in Tobacco Cultivation in Bengawan Solo - Larasanti, Novia; Dwisatyadini , Mutimanda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This study aims to evaluate the effectiveness of controlling Heliothis virescens infestation and Pseudomonas syringae Infection using synthetic pesticides on Nicotiana tabacum cultivation In Bengawan Solo, East Java, Indonesia. Results showed a decrease In pest density (from 6.8 to 3.7 individuals per plant), disease Intensity (from 52.0% to 30.7%), and leaf damage (from 48.5% to 26.4%). Furthermore, statistical analysis revealed significant differences between treatments (p < 0.05). Mechanical control significantly reduced the Incidence of pests and diseases In tobacco cultivation, with suppression efficiencies reaching 46.5% and 41.0%, respectively . In conclusion, farmer-led mechanical control Is an effective, low-cost, and sustainable strategy for managing pests and diseases In tobacco cultivation under tropical agroecological conditions, with potential to reduce dependence on synthetic pesticides and support environmentally friendly agricultural practices.